Mediterranean knowledge-potentialities in social work education. - López Peláez, Antonio; Pérez-García, Raquel; Castillo-de-Mesa, Joaquín (My University, 2017)
This symposium seeks to reflect and promote the academic, knowledge and scientific development of social work professional practice utkising a critical and sustainable approach to social work practice. Recognition of in socio-economic, cultural and political domains, which are characterized by cultural, ethnic and environmental diversity, is critical within society context which are committed to the values of solidarity and human rights. We intend to provide contributions for the reconfiguration of an educational model in social work development. Additionally we aim to explore the potential of Mediterranean knowledge for the Education in Social Work focusing in the new definition of Social Work (2014) and integrating theoretical, scientific and indigenous knowledge. From a holistic to an interdisciplinary approach gathering knowledge and life experiences, reconfiguring the Social Work pedagogical teaching frame into a paradigmatic basis: systemic, structuralist and ecological.
Keywords: Trabajo social - Mediterráneo (Región); Mediterranean knowledge; Innovation; Neo-liberalism; Education